Effects of esculentoside A on turnour necrosis factor production by mice peritoneal macrophages - Fang Jun; Zheng Qin Yue; Wang Hong Bin; Ju Dian Wen; Yi Yang Hua (Mediators of Inflammation)
Esculentoside A (EsA) is a saponin isolated from the roots of Phytolacca esculenta. Previous experiments showed that it had strong anti-inflammatory effects. Tumour necrosis factor (TNF) is an important inflammatory mediator. In order to study the mechanism of the anti-inflammatory effect of EsA, it was determined whether TNF production from macrophages was altered by EsA under lipopolysaccharide (LPS) stimulated conditions. EsA was found to decrease both extracellular and cell associated TNF production in a dose dependent manner at concentrations higher than 1 μmol/l EsA. Previous studies have showed that EsA reduced the releasing of platelet activating factor (PAF) from rat macrophages. The reducing effects of EsA on the release of TNF and PAF may explain its anti-inflammatory effect.